2021
DOI: 10.3390/infrastructures6110154
|View full text |Cite
|
Sign up to set email alerts
|

Observed Risk and User Perception of Road Infrastructure Safety Assessment for Cycling Mobility

Abstract: The opportunities for data collection in smart cities and communities provide new approaches for assessing risk of roadway components. This paper presents and compares two different methodological approaches for cycling safety assessment of objective and perceived risk. Objective risk was derived from speed and direction profiles collected with Global Navigation Satellite System (GNSS) and camera installed on an instrumented bicycle. Safety critical events between cyclists and other road users were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Figure 9 shows cycle track termini at the highest risk rank followed by the roundabout. The normalized Risk Rate are also calculated to allow for comparisons with the observed risk rate reported in previous study [9]. It should be noted that in Fig.…”
Section: Validation Through Case Study and Risk Assessmentmentioning
confidence: 96%
See 1 more Smart Citation
“…Figure 9 shows cycle track termini at the highest risk rank followed by the roundabout. The normalized Risk Rate are also calculated to allow for comparisons with the observed risk rate reported in previous study [9]. It should be noted that in Fig.…”
Section: Validation Through Case Study and Risk Assessmentmentioning
confidence: 96%
“…Despite the promising results, they concluded that more granular data and validation work needs to be done to improve the reliability of the correlation. Perceived risk resulted consistently with frequency of CSEs in bicycle paths classified by a panel of experts analyzing video recording and speed and heading GPS data [9]. All these research mainly rely on the identification of safety-critical events via self-reporting, manual review of video footage preselected thresholds and statistical methods to analyze data.…”
Section: Observational Studiesmentioning
confidence: 99%
“…Another research focused on the turning behavior of cyclists by measuring steering torque and angle, and bicycle speed, acceleration, and angular velocity [15,16], whereas in [17] the hard breaking behavior was studied by analyzing speed and acceleration signals and detecting the abnormal signals after applying signal processing techniques. In another research, cycling safety was assessed from objective and perceived points of view, where the risk classification of the roadway components was compared [18].…”
Section: Introductionmentioning
confidence: 99%